Identifikasi Jenis Tumbuhan Aromatik di Hutan Tembawang Bengap Desa Sape Kabupaten Sanggau - Calaudianus Feri, Yosep; Yusro, Fathul; Dirhamsyah, Muhammad; Mariani, Yeni (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2025)
Tembawang forest is a form of local wisdom practiced by the people of Kalimantan in managing land sustainably, preserving high biodiversity, including aromatic plants. One of the tembawang forests that holds potential for aromatic plants and is utilized by battra (traditional healers) is the Bengap Tembawang Forest, located in Sape Village, Sanggau Regency. This study aims to identify the species of aromatic plants found in the Tembawang Bengap Forest, Sape Village, Sanggau Regency, West Kalimantan. The method used is qualitative descriptive with an exploratory approach through semi-structured interviews with battra (traditional healers), followed by species identification in the field based on morphological and organoleptic characteristics. The results of the study revealed 13 aromatic plant species from 8 botanical families, with growth forms consisting of trees (7 species), herbs (5 species), and shrubs (1 species). The plant parts used include leaves, stems, roots, and fruits. Their utilization is classified into two main functions: as traditional medicine for coughs, fevers, and digestive disorders, and as food ingredients and cooking spices. These findings highlight the importance of aromatic plants for battra in traditional medicine and daily culinary practices, while also demonstrating the functional and cultural values of aromatic plants in the tembawang ecosystem.